(untitled) (Nepal Medical College Journal, 2022)
Although root canal treatment is carried out to eliminate the existing microorganism and create favorable environment for healing and prevent reinfection, the occurrence of post treatment disease poses a significant challenge in general population. Cross sectional studies from different countries shows that there is varying degree of prevalence of periradicular radiolucencies (PR) in root filled teeth. Since no such prevalence studies have been done in Nepal, we are unaware of the existing problem in our population. Thus, aim of this study was to investigate the prevalence of periradicular radiolucencies and its association with the quality of root canal treatment and coronal restorations in an adult Nepali population. Among 350 patients, 40.8% (389) presented with PR. Significantly better outcome was seen in teeth with adequate qualities of root filled teeth and coronal restoration. The prevalence of PR in Nepali population was seen relatively high and the considerable efforts to improve the length control during the procedure followed by proper restoration, to lessen the development of PR cannot be over emphasized.